Aktivitas biopreservatif asap cair Cangkang sawit dalam menghambat Bakteri patogen dan pembusuk=(The Biopreservative Activity of Liquid Smoke of Palm Kernel Shell on the Repression of Patogenic and Spoilage Bacteria) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT Biopreservative activities of five fractions of liquid smoke of palm kernel shell had been tested on four bacteria cultures i.e. Escherichia coli, Staphy-lococcus aureus, Bacillus subtilis dan Pseudomanas fluorescens. The purpose of this research were to evaluate activities of liquid smoke of palm kernel shell for the biopreservative on patogenic and spoilage bacteria. This research was started from liquid smoke fractionation of temperature variation